Fusarium oxysporum var. redolens from Africa as a cause of vascular wilt disease of oil palm - Ho, Yin Wan; Varghese, George; Taylor, G. S. (Wiley, 1985)
The vascular wilt disease of oil palm (Elaeis guineensis Jacq.) was first reported by Wardlaw in Zaire (1946a, b). Since then, the disease has been reported in other parts of Africa. So far, Fusarium oxysporum Schl. f. sp. elaeidis Toovey has been documented as the causal agent of the vascular wilt disease in oil palm. Now F. oxysporum var. redolens is shown to be also involved.